2010
DOI: 10.1111/j.1600-079x.2010.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of melatonin by taurine chloramine

Abstract: Melatonin is widely known for its antioxidant, immunomodulatory, and anti-inflammatory effects. Hypochlorous acid (HOCl) is one example of an endogenous oxidant that is promptly neutralized by melatonin. Melatonin also inhibits myeloperoxidase, the enzyme that catalyzes the oxidation of chloride to HOCl. Taurine is the most abundant free amino acid in leukocytes. In activated neutrophils, taurine is converted to taurine chloramine (Tau-NHCl) through a reaction with HOCl. In addition, the related compound tauri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…N 1 -Acetyl- N 2 -formyl-5-methoxykynuramine (AFMK) is a product of melatonin oxidation, which can involve both enzymatic and non-enzymatic processes [ 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 ]. AFMK has an excellent ability as a • OH scavenger [ 287 , 288 , 289 , 290 ].…”
Section: Antioxidant Protectionmentioning
confidence: 99%
“…N 1 -Acetyl- N 2 -formyl-5-methoxykynuramine (AFMK) is a product of melatonin oxidation, which can involve both enzymatic and non-enzymatic processes [ 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 ]. AFMK has an excellent ability as a • OH scavenger [ 287 , 288 , 289 , 290 ].…”
Section: Antioxidant Protectionmentioning
confidence: 99%
“…In addition, oxidation of melatonin was partially inhibited by catalase or SOD . Finally, it has been reported that taurine, the most abundant free amino acid in leukocytes, undergoes an oxidation to taurine chloramines by HClO, and this compound oxidizes melatonin to 2‐hydroxymelatonin and AFMK .…”
Section: Neutrophilsmentioning
confidence: 99%
“…The rate constants were (pH 5.0) 1.1 × 10 4 M −1 s −1 , (pH 7.0) 9.5 × 10 1 M −1 s −1 and (pH 9.0) 1.7 × 10 1 M −1 s −1 . The pH dependence can be explained by taking into account the higher reactivity of the dihalogenated forms, as has been demonstrated for Tau-NCl 2 [ 45 ].…”
Section: Resultsmentioning
confidence: 99%